Cryo-Electron Microscopy Modeling by the Molecular Dynamics Flexible Fitting Method - Chan, Kwok-Yan; Trabuco, Leonardo G.; Schreiner, Eduard; Schulten, Klaus (Biopolymers, 2012)
The increasing power and popularity of cryo-electron microscopy (cryo-EM) in structural biology brought about the development of so-called hybrid methods, which permit the interpretation of cryo-EM density maps beyond their nominal resolution in terms of atomic models. The Cryo-EM Modeling Challenge 2010 is the first community effort to bring together developers of hybrid methods as well as cryo-EM experimentalists. Participating in the challenge, the molecular dynamics flexible fitting (MDFF) method was applied to a number of cryo-EM density maps. The results are described here with special emphasis on the use of symmetry-based restraints to improve the quality of atomic models derived from density maps of symmetric complexes; on a comparison of the stereochemical quality of atomic models resulting from different hybrid methods; and on application of MDFF to electron crystallography data. © 2012 Wiley Periodicals, Inc. Biopolymers 97: 678-686, 2012.